Impact of emotional intelligence and perceived self-efficacy on the implementation of community policing practice - Happiness, Okoka; J. G, Kheswa; Iliya, Vakpa (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
This study aimed to investigate the association between emotional intelligence, perceived self-efficacy (PSE) and implementation of community policing practice among police officers in the Nigeria Police Force. This study involved 107 police officers as participants who were selected through purposive random sampling. Data were collected using emotional intelligence, perceived self-efficacy (PSE) and implementation of community policing practice scales. Data were analysed using a regression analysis and partial correlation technique to test the Hypotheses. The study found weak, counterintuitive negative correlations between both emotional intelligence and perceived self-efficacy and community policing implementation in Nigerian police. Emotional intelligence positively associates with implementation, but perceived self-efficacy does not, demanding further context-specific qualitative and longitudinal research to understand these dynamics and improve policing strategies. The study highlights the importance of emotional intelligence and self-efficacy for successful community policing practice among police officers in Nigeria. The results imply how the Nigeria Police Force can enhance the officers’ implementation of the community policing practice by managing their self-efficacy and increasing emotional intelligence.